The Influence Of Emotional Marketing And Experiential Marketing On Purchasing Decisions In E-commerce tiktok shop (Case Study Of Uncip Students) - Imam Budi Darmawan; Isyana Rahayu (Citakonsultindo, 2026)
This study aims to analyze the influence of Emotional Marketing and Experiential Marketing on consumer purchase decisions on the TikTok Shop e-commerce platform, with a case study on students of Cipasung University (UNCIP) Faculty of Economics and Business class of 2022. The research method used is quantitative descriptive with a verifiable approach. The sample amounted to 85 respondents who were selected using the purposive sampling technique based on the Slovin formula with an error rate of 10%. Data were collected through a five-point Likert scale questionnaire and analyzed using validity tests, reliability tests, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation, and linearity), multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the help of SPSS version 26. The results showed that (1) Emotional Marketing had a positive and significant effect on purchase decisions (t = 2.074; sig. = 0.041); (2) Experiential Marketing has a positive and significant effect on purchase decisions (t = 6,953; sig. = 0.000); and (3) simultaneously, the two variables were able to explain 69.3% of the variation in purchasing decisions (R² = 0.693; F = 92,452; sig. = 0.000). These findings indicate that emotion- and experiential-based marketing strategies are crucial factors in driving young consumers' purchasing decisions on social commerce platforms.